2022
DOI: 10.3389/fmicb.2022.1035904
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic bacteria significantly increased under oxygen depletion in coastal waters: A continuous observation in the central Bohai Sea

Abstract: The spread of pathogenic bacteria in coastal waters endangers the health of the local people and jeopardizes the safety of the marine environment. However, their dynamics during seasonal hypoxia in the Bohai Sea (BHS) have not been studied. Here, pathogenic bacteria were detected from the 16S rRNA gene sequencing database and were used to explore their dynamics and driving factors with the progressively deoxygenating in the BHS. Our results showed that pathogenic bacteria were detected in all samples, accounti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…These microorganisms' interactions with environmental parameters serve as indicators that reflect the function and structure of marine ecosystems, as highlighted in previous studies (Boucher et al, 2006). For instance, the community structure and dynamics of bacteria belonging to Proteobacteria, Firmicutes, and Actinobacteriota phyla appeared to be affected by various factors such as salinity, dissolved oxygen, ammonia, phosphate and silicate concentrations (Guo et al, 2022b). Although variations in microbial community can be substantial across different habitat types, primarily due to the impact of environmental gradients (Martiny et al, 2006), some studies suggested consistency in community composition across similar habitats, regardless of geographical distance (Lauber et al, 2009).…”
Section: Introductionmentioning
confidence: 71%
“…These microorganisms' interactions with environmental parameters serve as indicators that reflect the function and structure of marine ecosystems, as highlighted in previous studies (Boucher et al, 2006). For instance, the community structure and dynamics of bacteria belonging to Proteobacteria, Firmicutes, and Actinobacteriota phyla appeared to be affected by various factors such as salinity, dissolved oxygen, ammonia, phosphate and silicate concentrations (Guo et al, 2022b). Although variations in microbial community can be substantial across different habitat types, primarily due to the impact of environmental gradients (Martiny et al, 2006), some studies suggested consistency in community composition across similar habitats, regardless of geographical distance (Lauber et al, 2009).…”
Section: Introductionmentioning
confidence: 71%
“…Disease/Parasites: Under low oxygen conditions, some parasitic and microbial infections can become more common or severe, affecting both individuals and populations. Certain types of pathogenic bacteria start to grow under low-oxygen conditions, increasing organisms' likelihood of exposure (Guo et al, 2022). In addition, low-oxygen effects on host immune responses are common.…”
Section: Species/populationmentioning
confidence: 99%
“…The growth of pathogenic bacteria in marine water is influenced by various aspects, including temperature, pH value, dissolved oxygen, and salinity. Moreover, higher concentrations of nutrients in association with suspended matter have been recorded to boost the persistence of pathogenic bacteria in coastal marine water [10,11]. The excessive use of antibiotics has led to the reduction of susceptible pathogenic bacteria and the increment of resistant populations against multiple antibiotics.…”
Section: Introductionmentioning
confidence: 99%